The Use of Ultrasonic Pulse Velocity (UPV) Method in Evaluating Structural Damage of Mooring Dolphin Following a Ship Incident (Case Study: Repair of Mooring Dolphin – Pertamina, Tg. Uban) - Muhammad Andika Rivaldo; Indrastuti (Journal of Civil Engineering and Planning (JCEP), 2024)
Mooring Dolphin is an important port infrastructure that often receives high dynamic loads and is at risk of damage due to ship collisions, as occurred in Tanjung Uban, where the Mooring Dolphin owned by PT Pertamina was damaged after a collision with a vessel from PT Soechi Lines. This study uses the Ultrasonic Pulse Velocity (UPV) method as part of a Non-Destructive Test (NDT) to evaluate the level of structural damage. UPV works by measuring the speed of ultrasonic waves through concrete to identify cracks, voids, or weak zones. Testing was conducted on the upper and lower structures of the Mooring Dolphin, with results showing cracks ranging in depth from 2 to 15 cm and widths of 0.2 to 1.5 mm, particularly in the areas directly affected. Most of the structure showed wave speeds above the safe threshold, indicating that the integrity of the concrete is relatively good; however, zones with low wave speeds were found that require repair. This study demonstrates that the UPV method is effective in providing detailed information about the location and extent of damage to support repair processes. Technical recommendations include epoxy injection in cracks and additional reinforcement in critical areas to enhance the structure's resistance to dynamic loads. The findings of this study are expected to serve as a reference for the evaluation and repair of port structures that experience similar damage.